Оценка эффективности внешнеэкономической деятельности ("Journal "U". Economy. Management. Finance.", 2021)
The object of the study is the effective foreign economic activity of commercial enterprises.The purpose of the study is to evaluate the effectiveness of foreign economic activity and increase the efficiency of foreign trade operations.The results of the study: the methodology of assessing the effectiveness of foreign economic activity both in general and in terms of improving the efficiency of foreign trade operations with the use of international rules of interpretation of INCOTERMS 2020, knowledge of the provisions of international documents regulating foreign economic activity, agreements, calculation of economic justification.
Keywords: foreign economic activity; profit; profitability; turnover; economic efficiency; business process